Analysis of Ease of Access to Investment Features and Trust in Security on Investment Decisions of Livin’ by Mandiri Users with User Attitude as a Mediating Variable - Husein, Muhammad Zaidan (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
In the current digital era, the advancement of information and communication technology has transformed many aspects of life, including investment. Mobile applications have become one of the primary solutions for individuals looking to invest more easily and quickly. One prominent application in this field is "Livin’ by Mandiri," which offers various investment features designed to help users manage their portfolios. The ease of access to investment features within this application is a crucial factor influencing users’ investment decisions. Good accessibility allows users to execute transactions, monitor investment performance, and obtain necessary information quickly. However, this ease is not sufficient with just a user-friendly design, the trust in the application’s security also plays a critical role. Users need to feel secure that their personal data and financial transactions are protected from potential threats. Trust in the application’s security is one of the key elements in determining investment decisions. Users who feel safe are more likely to confidently conduct transactions and make larger investment decisions. Conversely, a lack of trust can hinder users from utilizing available investment features, even if accessibility is good. User attitude also serves as an intervening variable that affects the relationship between ease of access to features and trust in security with investment decisions. A positive attitude towards the application can enhance user trust and encourage them to make more active investment decisions. On the other hand, a negative attitude can be a barrier, even when the application provides easily accessible and secure features. This research aims to analyze the relationship between the ease of access to investment features, trust in the security of the Livin’ by Mandiri application, and users’ investment decisions, considering user attitude as an intervening variable. By understanding this relationship, it is hoped that better insights can be gained regarding the factors influencing investment decisions, as well as assisting application developers in enhancing user experience. Through this research, it is expected to make a significant contribution to developing more effective and secure investment applications, supporting users in making smarter and more informed investment decisions. Thus, this research is not only relevant for academics and researchers but also for industry practitioners and users of investment applications.